Polyethylene Glycol 3350 in the Treatment of Chronic Idiopathic Constipation: Post hoc Analysis Using FDA Endpoints - Menees, Stacy B.; Lembo, Anthony J.; Chey, William D. (Canadian Journal of Gastroenterology and Hepatology, 2022)
Background & Aims. The efficacy and safety of polyethylene glycol 3350 for chronic idiopathic constipation have been demonstrated in randomized controlled trials. A new US Food and Drug Administration-recommended primary efficacy endpoint for evaluating chronic idiopathic constipation prompted our reevaluation of previously reported clinical data with polyethylene glycol 3350. Methods. This multicenter, double-blind, placebo-controlled, parallel-group trial included adults with chronic idiopathic constipation randomized to polyethylene glycol 3350 17 g (n = 204) or placebo (n = 100) once daily for 24 weeks. Post hoc analyses were performed using the US Food and Drug Administration endpoint (≥3 complete spontaneous bowel movements/week and an increase of ≥1 complete spontaneous bowel movement/week from baseline for ≥9/12 weeks, including 3 of the last 4 weeks) along with additional efficacy and safety outcomes. Results. The proportion of patients meeting the new endpoint was significantly higher with polyethylene glycol 3350 vs placebo (42% vs 13%; P<0.0001). Reductions in the mean number of hard/lumpy stools/week (–2.1 vs –0.9; P=0.0014) and the weekly mean five-point cramping rating (–0.3 vs –0.1; P=0.0272) also significantly favored polyethylene glycol 3350. The proportion of subjects with gastrointestinal adverse events decreased markedly after the first week of treatment in the polyethylene glycol 3350 group. Conclusion. Using the current US Food and Drug Administration-recommended responder definition and other secondary outcomes, once-daily polyethylene glycol 3350 demonstrated substantial and sustained efficacy and safety over 24 weeks in patients with chronic idiopathic constipation. Trial Registration. The original trial was registered with https://clinicaltrials.gov Trial: NCT00153153.